Duration of Acute Kidney Injury and In-Hospital Mortality in Elder Patients with Severe COVID-19: A Retrospective Cohort Study. (26th July 2022) - Cai, Yue; Tang, Chong; Song, Yun; Li, Qinglin; Guo, Shanshan; Chen, Yanyan; Wang, Fang; Li, Yangping; Lei, Yan; Li, Fei; Tao, Ling
Abstract : Background . Patients with severe coronavirus disease 2019 (COVID-19) who develop acute kidney injury (AKI) in the intensive care unit (ICU) have extremely high rates of mortality. This study evaluated the prognostic impact of AKI duration on in-hospital mortality in elder patients. Methods . We performed a retrospective study of 126 patients with confirmed COVID-19 with severe or critical disease who treated in the ICU from February 4, 2020, to April 16, 2020. AKI was defined according to the Kidney Disease Improving Global Outcomes serum creatinine (Scr) criteria. AKI patients were divided into transient AKI and persistent AKI groups based on whether Scr level returned to baseline within 48 h post-AKI. Results . In total, 107 patients were included in the final analysis. The mean age was 70 (64–78) years, and 69 (64.5%) patients were men. AKI occurred in 48 (44.9%) during their ICU stay. Of these, 11 (22.9%) had transient AKI, and 37 (77.9%) had persistent AKI. In-hospital mortality was 18.6% (n = 11 ) for patients without AKI, 72.7% (n = 8 ) for patients with transient AKI, and 86.5% (n = 32 ) for patients with persistent AKI (P < 0.001 ). Kaplan–Meier curve analysis revealed that patients with both transient AKI and persistent AKI had significantly higher death rates than those without AKI (log-rank P < 0.001 ). Multivariate Cox regression analysis revealed that transient and persistent AKI were an important risk factor for in-hospital mortality in older patients with severe COVID-19 even after adjustment for variables (h a z a r d r a t i o H R = 2.582 ; 95% CI: 1.025–6.505; P = 0.044 ; and H R = 6.974 ; 95% CI: 3.334–14.588; P < 0.001 ). Conclusions . AKI duration can be an important predictive parameter in elder patients suffering from COVID-19 and are admitted to ICU. Among these patients, those exhibiting persistent AKI have a lower in-hospital survival rate than those with transient AKI, emphasizing the importance of identifying an appropriate treatment window for early intervention.